If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(p + -9) = 12(p + -7) Reorder the terms: 3(-9 + p) = 12(p + -7) (-9 * 3 + p * 3) = 12(p + -7) (-27 + 3p) = 12(p + -7) Reorder the terms: -27 + 3p = 12(-7 + p) -27 + 3p = (-7 * 12 + p * 12) -27 + 3p = (-84 + 12p) Solving -27 + 3p = -84 + 12p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-12p' to each side of the equation. -27 + 3p + -12p = -84 + 12p + -12p Combine like terms: 3p + -12p = -9p -27 + -9p = -84 + 12p + -12p Combine like terms: 12p + -12p = 0 -27 + -9p = -84 + 0 -27 + -9p = -84 Add '27' to each side of the equation. -27 + 27 + -9p = -84 + 27 Combine like terms: -27 + 27 = 0 0 + -9p = -84 + 27 -9p = -84 + 27 Combine like terms: -84 + 27 = -57 -9p = -57 Divide each side by '-9'. p = 6.333333333 Simplifying p = 6.333333333
| a-8=3 | | y^2+3y+2y+2=0 | | 2(x+8)=12(x-10) | | -12p+1=-xp+16 | | (-9-3i)(2+i)= | | -16+4x+1=5 | | 2x-y-z=-3 | | 7/x-3-1/2=3/x-4 | | 17=3x-19 | | 5(n-12)=12(n-9) | | Xp=12p+15 | | A=zv+q | | 12X^3/3X^2 | | 20y-5y=15-5y+5 | | 3/c=3/7 | | 6(a-12)=9(a+10) | | 2x-5/9 | | c/3=3/7 | | 3x-2[x+4(x-5)+3]=2x-2 | | 5(m-8)=12(m-10) | | (10t-15)=(7t) | | 2y+4-8y=6+5y+9 | | 3(2x-5)+3=2x+4 | | 9*n+10=100 | | y=sin(30)*5 | | 3(r+5)=11(r+9) | | 6x+14=8x-22 | | 8a+3b=152.50 | | (5t)=(40) | | 3x+7=5(x-2) | | e=7-10 | | 19/4x-1=5 |